Ein modellbasiertes Messverfahren zur Charakterisierung von Piezokeramiken unter Verwendung eines einzelnen scheibenförmigen Probekörpers - Feldmann, Nadine
Designprozesse von Schallwandlern werden durch zunehmende Rechenkapazitäten immer mehr durch simulative Betrachtungen unterstützt. Dabei ist vor allem die Wahl der Materialparameter der verwendeten Materialien wichtig für ein realitätsnahes Simulationsergebnis. Bei Schallwandlern werden häufig Piezokeramiken als aktive Elemente genutzt, welche sich durch eine Verkopplung mechanischer und elektrischer Eigenschaften auszeichnen. Zur Bestimmung ihrer Materialparameter stellt der IEEE Standard on Piezoelectricity ein standardisiertes Verfahren dar. Dazu sind fünf Impedanzmessungen an vier unterschiedlich gefertigten Probekörpergeometrien notwendig. Da an jedem einzelnen Probekörper nur eine Untermenge aller notwendigen Materialparameter bestimmt werden kann, werden diese dann zu einem kompletten Materialparametersatz zusammengefügt. Aufgrund der unterschiedlichen Prozessbedingungen, bei denen die jeweiligen Probekörper hergestellt werden, ist dieser Materialparametersatz jedoch inkonsistent und kann nie das Verhalten einer einzelnen Probe beschreiben. Daher wird in der vorliegenden Arbeit ein Messverfahren entwickelt, mit dem es möglich ist, alle relevanten Materialparameter unter besonderer Berücksichtigung von Dämpfung an einem einzelnen Probekörper allein durch Impedanzmessungen zu bestimmen. Als Probekörper wird dazu eine in der Anwendung häufig verwendete Scheibengeometrie verwendet. Um eine hinreichend hohe Sensitivität auf alle Materialparameter zu gewährleisten, wird diese mit einer optimierten Elektrodentopologie gefertigt. Da in diesem Fall keine analytische Betrachtung mehr möglich ist, wird das Messverfahren durch einen inversen Ansatz realisiert.

1/f-Frequency Fluctations and Phase Noise in MEMS Resonators - Handel, Peter; Henning, Bernd
The classical forms of noise present in the frequency of MEMS resonators have been recently investigated and described in detail. The present paper extends this investigation to 1/f noise. That is of fundamental nature in microelectromechanical systems (MEMS) resonators, and is given by the universal quantum 1/f effect. In recent years new piezoelectric and compound semiconductor materials have been developed along with advanced manufacturing technologies for MEMS including them. These technologies enable the deposition of thin compound semiconductor, or PZT films and their integration into MEMS devices.

2D phononic crystal sensor with normal incidence of sound - Zubtsoc, Mikhail; Lucklum, Ralf; Ke, Manzhu; Oseev, Alexandr; Grundmann, Ralf; Henning, Bernd; Hempel, Ulrike (Sensors and Actuators A: Physical)
The contribution presents the sensor application of a resonance-induced extraordinary transmission through a regular phononic crystal consisting of a metal plate with a periodic arrangement of holes in a square lattice at normal incidence of sound. The characteristic transmission peak has been found to strongly depend on sound velocity of the liquid the plate is immersed in. The respective peak maximum frequency can serve as measure for the concentration of a component in the liquid mixture, if a beneficial relation to the speed of sound of the liquid exists. Experimental verification has been performed with mixtures of water and propanol as model system. Here we especially pay attention to numerical calculations based on EFIT and COMSOL which reveal more insides to the wave propagation characteristics. Experimental investigations with Schlieren method and laser interferometry support the theoretical findings.

3.2 - Infrared reflectance measurements of thin films with time variable surface roughness or texture - Hoof, C.; Wetzlar, D.; Henning, Bernd

3.2.3 - Direktgravimetrischer Partikelmasse-Sensor zur quasikontinuierlichen Emissionsmessung - Ester, S.; Struschka, M.; Henning, Bernd

5.3.1 - Ein ultraschallbasiertes inverses Messverfahren zur Charakterisierung viskoelastischer Materialparameter von Polymeren - Bause, F.; Henning, Bernd

A Comparison of Alternative Ways to Identify Singular Matrices - Walther, Andrea; Bause, Fabian; Henning, Bernd

A DC bias approach to the characterisation of non-linear material parameters of piezoelectric ceramics - Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd
Keywords: piezoelectric materials; piezoelectric properties; DC bias field; non-linear material parameters

A modified electrode topology with increased sensitivity of electrical impedance to piezoelectic material parameters - Kulshreshtha, Kshitij; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten

A modular, scalable open-hardware platform for project-based laboratory courses in electrical engineering studies - Hetkämper, Tim; Krumme, Matthias; Dreiling, Dmitrij; Claes, Leander (SEFI 48th Annual Conference Proceedings - Engaging Engineering Education)

A new method of spatial filtering for Schlieren visualization of ultrasound wave fields - Unverzagt, Carsten; Olfert, Sergei; Henning, Bernd (Physics Procedia)

A sensitivity-based optimisation procedure for the characterisation of piezoelectric discs - Feldmann, Nadine; Jurgelucks, Benjamin; Claes, Leander; Henning, Bernd (2019 International Congress on Ultrasonics)

A Space Optimization Method for Time-Reversal Super-Focusing - Rautenberg, Jens; Olszewski, Dirk; Henning, Bernd (Proceedings of the Joint Congress CFA/DAGA 2004)
The appliance of time-reversal acoustics to classical trans-ducer design, medical, technical or audible range applica-tions brings forward new ideas whenever we need both, focusing acoustical energy in time and space. Unfortunately, the spatiotemporal focusing is limited through the amount of applied transducer elements as well as the ergodicity and randomness of the cavity [1]. This paper will show how the simulated annealing technique, a multi-objec¬tive optimiza-tion algorithm [2], is used to increase the nar¬rowness of the refocused spot by breaking up randomness for the benefit of ergodicity in a predetermined cavity.

A Spectral Approach to Acoustic Absorption Measurement - Claes, Leander; Chatwell, René Spencer; Vrabec, Jadran; Henning, Bernd (PROCEEDINGS -- AMA Conferences 2017)

A3.2 - Design, modeling and identification of an ultrasonic composite transducer for target impedance independent short pulse generation - Bause, F.; Rautenberg, J.; Henning, Bernd

Acoustic absorption measurement for the determination of the volume viscosity of pure fluids / Messverfahren für die akustischen Absorption zur Bestimmung der Volumenviskosität reiner Fluide - Claes, Leander; Hülskämper, Lars Moritz; Baumhögger, Elmar; Feldmann, Nadine; Chatwell, René Spencer; Vrabec, Jadran; Henning, Bernd (tm - Technisches Messen)

Acoustic Material Characterization of Additively Manufactured Components - Claes, Leander; Jäger, Axel; Johannesmann, Sarah; Webersen, Manuel; Kupnik, Mario; Henning, Bernd (PROCEEDINGS -- AMA Conferences 2017)

Acoustic material characterization of prestressed, plate-shaped specimens - Johannesmann, Sarah; Brockschmidt, Tobias; Rump, Friedhelm; Webersen, Manuel; Claes, Leander; Henning, Bernd (Sensoren und Messsysteme)

Acoustic properties of highly attenuating isotropic media - Rautenberg, Jens; Henning, Bernd
In the 1950's many investigations have been made in measuring the Young's and the shear modus of isotropic materials with acoustic waves. Therefore both the longitudinal and transversal sound velocities have been determined with only one specimen, that had to be large in comparison to the wavelength (Brown, Reynolds, Dunegan). Therewith the method was suited only for low absorbing materials. In the 1990's further developments led to mono mode rods to describe viscoelastic properties. Their diameters had to be very small for high frequencies, thus giving practical values up to 65 kHz (Benatar). This contribution is about a tubular multi mode specimen and its application for the simultaneous measurement of the abovementioned acoustic properties at high frequencies.

Acoustical waveguides for sensor applications - Henning, Bernd; Rautenberg, Jens
The continuous measurement of rheological properties (density and viscosity) or material properties (concentration of selected substances) of liquid mixtures in the chemical industry or in the food industry is a great challenge to this day. Standard chemical sensors are often not suitable for industrial processes because of their slow sensor response and their limited robustness due to the direct contact to process media. Ultrasonic sensor systems meet the practical requirements of a chemical sensor quite well. Current ultrasonic sensor systems are already widely used as acoustic chemical sensors to measure concentration of selected substances or to monitor the course of polymerization, crystallization or fermentation processes. Useable acoustic properties for the characterization of liquid mixtures are sound velocity, sound absorption and acoustic impedance in consideration of temperature. This contribution will give a short overview of the state of the art and several trends for the use of ultrasonic sensor systems in process applications. Currently there are many activities to use acoustic waveguides for above mentioned sensor applications. By means of two selected examples (density measurement and determination of acoustic properties of highly absorbing synthetic polymers) it will presented new developed measurement principles using acoustic waveguides.

Adaptives Mode-Tracing und numerische Stabilisierung modellierter Anregungsstrukturen für die halbanalytische Simulation geführter Wellen - Bause, Fabian; Henning, Bernd

Additiv gefertigte, akustische Diffusor-Strukturen für Ultraschallanwendungen - Claes, Leander; Zeipert, Henning; Koppa, Peter; Tröster, Thomas; Henning, Bernd

Additively manufactured acoustic diffuser structures for ultrasonic measurement applications - Claes, Leander; Zeipert, Henning; Koppa, Peter; Tröster, Thomas; Henning, Bernd (Proceedings of Meetings on Acoustics)

Akustische Charakterisierung der mechanischen Eigenschaften künstlich gealterter Polymere - Webersen, Manuel; Hüttner, Matthias; Woitschek, Fabian; Moritzer, Elmar; Henning, Bernd (Fortschritte der Akustik - DAGA 2019)

Akustische Charakterisierung der richtungsabhängigen elastischen Eigenschaften faserverstärkter Kunststoffe - Webersen, Manuel; Johannesmann, Sarah; Düchting, Julia; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2018)

An acoustic waveguide-based approach to the complete characterisation of linear elastic, orthotropic material behaviour - Johannesmann, Sarah; Düchting, Julia; Webersen, Manuel; Claes, Leander; Henning, Bernd (tm - Technisches Messen)
Keywords: Continous-fibre reinforced plastics; material parameters; orthotropy; ultrasonics

An approach to adhesive bond characterisation using guided acoustic waves in multi-layered plates - Zeipert, Henning; Claes, Leander; Johannesmann, Sarah; Lugovtsova, Yevgeniya; Nicolai, Marcel; Prager, Jens; Henning, Bernd (at - Automatisierungstechnik)
An approach for the non-destructive characterisation of adhesive bonds using guided ultrasonic waves is presented. Pulsed laser radiation is used to thermoacoustically excite broadband ultrasonic waves in a multi-layered sample, consisting of a metal plate adhesively joined to a polymeric layer using synthetic resin. The resulting signals are received by a purpose-built piezoelectric transducer. Varying the distance between excitation and detection yields spatio-temporal measurement data, from which the dispersive properties of the propagating waves can be inferred using a two-dimensional Fourier transform, assuming the plates to act as coupled waveguides. Coupled multi-layered waveguides show an effect referred to as mode repulsion , where the distance between certain modes in the frequency-wavenumber domain is assumed to be a measure of coupling strength. Measurements at different stages of curing of the adhesive layer are performed and evaluated. A comparison of the results shows changes in the dispersive properties, namely an increased modal bandwidth for the fully cured sample as well as an increased modal distance.

An Approach to Non-Destructive Testing of Aged Polymers - Moritzer, Elmar; Hüttner, Matthias; Henning, Bernd; Webersen, Manuel

An explicit symplectic approach to solving the wave equation in moving media - Inguva, Venkatesh; Feldmann, Nadine; Claes, Leander; Koturbash, Taras; Hahn-Jose, Thomas; Koutcherov, Vladimir; Kenig, Eugeny (Engineering Reports)
An explicit approach using symplectic time integration in conjunction with traditional finite difference spatial derivatives to solve the wave equation in moving media is presented. A simple operator split of this second order wave equation into two coupled first order equations is performed, allowing these split equations to be solved symplectically. Orders of symplectic time integration ranging from first to fourth along with orders of spatial derivatives ranging from second to sixth are explored. The case of cylindrical acoustic spreading in air under a constant velocity in a 2D square structured domain is considered. The variation of the computed time-of-flight, frequency, and wave length are studied with varying grid resolution and the deviations from the analytical solutions are determined. It was found that symplectic time integration interferes with finite difference spatial derivatives higher than second order causing unexpected results. This is actually beneficial for unstructured finite volume tools like OpenFOAM where second order spatial operators are the state-of-the art. Cylindrical acoustic spreading is simulated on an unstructured 2D triangle mesh showing that symplectic time integration is not limited to the spatial discretization paradigm and overcomes the numerical diffusion arising with the in-built numerical methods which hinder wave propagation.

An improved mode-tracing algorithm to compute dispersion curves of acoustic waveguides - Bause, Fabian; Rautenberg, Jens; Henning, Bernd
Semi-analytical approaches for the description of dispersion in acoustic waveguides are based on root finding in a characteristic function. A mode-tracing algorithm helps to find all solutions of this problem by consecutively bracketing single roots. In this contribution we present a multistage and adaptive mode-tracing algorithm, which uses an adaptive step size for the prediction of consecutive solutions as well as an adaptive estimation of the search space around these predictions. Furthermore we present a validation stage to ensure the correlation between consecutive solutions alias waveguide modes.

An inverse approach to the characterisation of material parameters of piezoelectric discs with triple-ring-electrodes - Feldmann, Nadine; Jurgelucks, Benjamin; Claes, Leander; Schulze, Veronika; Henning, Bernd; Walther, Andrea (tm - Technisches Messen)

Analoge Klangsynthese zur Vermittlung von Grundkenntnissen der Signalverarbeitung an Studierende nicht-technischer Fachrichtungen - Krumme, Matthias; Webersen, Manuel; Claes, Leander; Webersen, Yvonne (Fortschritte der Akustik - DAGA 2020)

Analyse integral erfasster rotationssymmetrischer Schallwechseldruckverteilungen in Schlierenabbildungen - Olfert, Sergei; Henning, Bernd

Analyse integral erfasster Schallwechseldruckverteilungen in Schlierenabbildungen - Olfert, Sergei; Henning, Bernd (XXIX Messtechnisches Symposium)

Analysis of Lamb wave mode repulsion and its implications to the characterisation of adhesive bonding strength - Lugovtsova, Yevgeniya; Johannesmann, Sarah; Henning, Bernd; Prager, Jens (2019 International Congress on Ultrasonics)

Analyzing the effect of adhered metal electrodes on piezoelectric elements using different types of adhesives - Bause, Fabian; Rautenberg, Jens; Henning, Bernd
Modeling and simulation play a key-role in computer-assisted design of ultrasonic sensors. The accuracy of those numerical or analytical models highly depends on the material dataset chosen as well as on the digitized simplified geometry. Thus, researchers worked on techniques how to measure material datasets of piezoceramics or passive materials (i.e. polymers) for use in simulation [Rau08] [Rup09]. Most computer models neglect the influence of adhesive bonds between those active and passive material components used to form a complete ultrasonic transducer and thus imply perfect interface layers. To gain a more accurate model one need to go further and consider non-perfect interface layers between assembly parts. Because adhesive bonds are neither necessarily isotropic nor homogeneous and their geometric dimensions are very small, we need to define effective material datasets dependent on the model used in simulation. In this contribution the indicator under study is the electric impedance of the active element. We will show the influence of different adhesives used to adhere metal electrodes on piezoceramic discs. Therefore, we use several different types of adhesives (epoxies, cyanoacrylates and perfluorpolyether grease) and different sizes of piezoceramic discs (PIC 255, manufacturer: PI Ceramic GmbH) of the same batch (thickness, diameter). The electrodes have been cut from one plate made of stainless steel using a laser to avoid uncertainty effects due to variations in material-parameters. The probes have been prepared in an air-conditioned Lab with constant temperature and humidity. The indicators considered to identify the effect of those different adhesive films are extracted from the electric impedance of the electromechanical converter.

Anwendungsm\"oglichkeiten der Schallfeldvisualisierung in der Ultraschallmesstechnik - Olfert, Sergei; Henning, Bernd

Application and modelling of ultrasonic transducers using 1-3 piezoelectric composites with structured electrodes - Dreiling, Dmitrij; Itner, Dominik; Feldmann, Nadine; Scheidemann, Claus; Gravenkamp, Hauke; Henning, Bernd (Fortschritte der Akustik - DAGA 2021)
Waveguide-based methods can be used for the non-destructive determination of acoustic material parameters. One of these methods is based on transmission measurements of cylindrical polymeric specimens. Here, the experimental setup consists of two transducers, which excite and receive the waveguide modes at the faces of the cylinder. The measurement, as well as a forward model, are used to determine material parameters of the polymeric specimen in an inverse approach. 1-3 piezoelectric composites are used as an active element because they can be approximated by a thickness vibration only. This allows an easy identification of Mason model parameters to characterise the transducers’ vibration behaviour. However, sensitivity analysis shows a high uncertainty in the determination of the mechanical shear parameters due to the uniform excitation. To increase the sensitivity to these shear motions, arbitrary excitations were investigated by means of numerical simulation. In order to be able to realise the determined optimal excitation, new transducer prototypes were designed. By subdividing the electrodes of the active element, for example, ring-shaped excitation is feasible. Furthermore, it can be shown that modelling these transducers with a one-dimensional Mason model is sufficient.

Application of Automatic Differentiation for the inverse parameter identification of complex-valued forward models - Webersen, Manuel; Bause, Fabian; Henning, Bernd

Application-based learning of signal analysis methods with the help of a graphical open-source software - Hetkämper, Tim; Koch, Kevin; Webersen, Manuel; Claes, Leander (SEFI 51th Annual Conference Proceedings - Engineering Education for Sustainability)

Approach of continuous characterisation of liquid multi-component mixtures - Gulsch, Michael; Henning, Bernd; Prange, Stefan; Auge, Jörg
Currently there are ultrasonic sensors to measure flow, liquid level, concentrations or to monitor the process course. In several processes the investigated media is a mixture of liquid and solid ingredients. The use of ultrasonic sensor systems will become very complicated if gas bubbles appear at the measurement place caused by chemical reactions, high temperature or fast flow this means under typical process conditions. The appearance of gas bubbles falsifies the measured absorption and also the velocity. The sound propagation in liquid mixtures is influenced in a complex manner for instance by solid particles, rapid changes of temperature, and liquid droplets of other density in the measured liquid simultaneously. For the detailed investigation of the influence of bubbles on sound propagation, an experimental setup was build. This setup permits the comprehensive processing of transmitted and scattered signals. Using a smart signal processing it is possible to find a reliable indication for gas bubbles.

Arbitrary sensitivity for inverse problems in piezoelectricity - Jurgelucks, Benjamin; Schulze, Veronika; Feldmann, Nadine; Claes, Leander

B5.4 - Signal Processing for Single Transducer Distance Measurement Applications to Reduce the Blind Zone - Schröder, A.; Henning, Bernd

Berührungslose Materialfeuchtemessung nach dem NIR-Prinzip bei schnell variierendem Messgutabstand - Wetzlar, Dietmar; Krumme, Matthias (4. CMM-Workshop Innovative Feuchtemessung in Forschung und Praxis)

Beschreibung des akustischen Verhaltens verklebter plattenförmiger Strukturen mittels Kopplungsmodellen - Zeipert, Henning; Hölscher, Jonas; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

Bestimmung der Volumenviskosität mittels akustischer Absorptionsmessung - Claes, Leander (Fortschritte der Akustik - DAGA 2023)

Bestimmung des Anteils ungelöster Gase in flüssigen Medien - Gulsch, Michael; Henning, Bernd
Impulsbasierte Ultraschallsensorsysteme zur Messung von Füllstand, Durchfluss und Konzentration sind heutzutage aufgrund ihrer Robustheit und Wartungsfreundlichkeit weit verbreitet. Probleme treten immer dann auf, wenn sich Gasblasen im Medium befinden. Diese verändern das empfangene Signal derart, dass eine exakte Messung der Schallgeschwindigkeit des flüssigen Mediums nicht mehr möglich ist. Dieser Beitrag behandelt eine neue Art der Signalauswertung, die eine zuverlässige Bestimmung der Schallgeschwindigkeit auch in diesem Fall gewährleistet. Darüber hinaus können auch Rückschlüsse auf den Gasanteil innerhalb des flüssigen Mediums gewonnen werden.

Blindzonenfreie Ultraschall-Abstandsmessung mit codierten Sendesignalen - Schröder, Andreas; Henning, Bernd
Bei der Ultraschall-basierten Abstandsmessung mit einem einzelnen Schallwandler ergibt sich durch das Prinzip bedingt eine Blindzone. Während und unmittelbar nach der Anregung durch das Sendesignal ist es im Allgemeinen nicht möglich, das Empfangssignal am Ultraschallwandler auszuwerten. Eine Verwendung von codierten Sendesignalen (z.B. zur Unterscheidung verschiedener Sensoren) verlängert diesen Blindbereich zusätzlich. Dieser Beitrag zeigt eine Möglichkeit zur Realisierung eines simultanen Sende- und Empfangsbetriebs mit einem einzelnen Schallwandler. Dadurch wird es möglich, die Blindzone auch bei sehr langen Sendesignalen zu eliminieren. Dazu wird der Ultraschallwandler über einen Vorwiderstand betrieben und dessen Spannung gemessen. Mittels eines mathematischen Modells kann das elektrische Sendesignal, welches am Ultraschallwandler anliegt, bestimmt werden. Die Subtraktion dieses Signals von der gemessenen Schallwandlerspannung liefert das elektrische Empfangssignal. Aufgrund von z.B. Temperatureinflüssen ändern sich die elektrischen Eigenschaften des Ultraschallwandlers ständig, wodurch eine Anpassung des Modells notwendig wird. Daher kann die Modellidentifikation nicht im Vorfeld mit einer Freifeldmessung erfolgen, sondern ist permanent während des Betriebes notwendig. Tritt dabei ein Empfangssignal z.B. infolge einer Reflexion auf, so wird die Bestimmung der Modellparameter gestört. Durch eine Bewertung der ermittelten Modelle kann die Robustheit einer Abstandsmessung erhöht werden

Bubble detection and gas volume measurement in bubble loaded liquids with pulse driven measurement devices - Gulsch, Michael; Henning, Bernd (2005 IEEE Ultrasonics Symposium)
Currently there are pulse based ultrasonic sensor systems used to measure flow, liquid level, concentration or in process monitoring. In several processes the investigated media are a mixture of liquid and solid ingredients (emulsions, suspensions). The use of ultrasonic sensor systems will be very complicated if gas bubbles appear at the measurement place caused by chemical reactions, high temperature or fast flow that means by typical process conditions. Firstly, the appearance of gas bubbles falsifies the measured absorption. Secondly, the measured velocity is influenced by gas bubbles. In figure 1 is visible that a volume fraction of 0.1 ppm of undissolved air decreases the sound velocity by 1.4 m s-1

Characterization of adhesion strength using guided ultrasonic waves - Nicolai, Marcel; Zeipert, Henning; Lugovtsova, Yevgeniya; Bulling, Jannis; Johannesmann, Sarah; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2023)